Evaluation of COVID-19 Vaccination Status among University’s Students, Academic and Nonacademic Staff in Mosul, Iraq - Omer Qutaiba Allela (Medical Journal of Babylon)
Background: The future frontline combatants in the fight against pandemics will be academic and nonacademic employees and health science students. A successful vaccination program requires an understanding of the factors that influence coronavirus disease 2019 (COVID-19) vaccine acceptance. Objective: The purpose of this study was to examine the influences on COVID-19 vaccination among the health sciences faculty and staff at Al-Noor University College, Mosul, Iraq. Materials and Methods: The study was a self-administered cross-sectional online survey that included employers and Al-Noor University College health sciences students. The individuals’ important information was gathered through the survey, which covered sociodemographic traits, COVID-19 infection, and vaccinations. To identify the COVID-19 vaccination variables, Statistical Package for the Social Sciences version 26 was used. Results: Most of the participants 77%, however, are single. More than 75% of participants were between the ages of 18 and 25 years; the majority were university students. Only 6% of participants held a doctor of philosophy, whereas 91% of participants were healthy. More than 80% of participants had vaccinations, with the Pfizer vaccine being the most common. Age groups and COVID-19 infection, immunizations, vaccine types, infection after vaccination, vaccination frequencies, COVID-19 infection frequencies, and period of infection were found to be significantly correlated. Conclusion: The health department may spread information about the COVID-19 vaccination to raise people’s impressions of their knowledge in light of the study’s findings. People could use anxiety-reduction strategies like mindfulness during the lockdown to assist them in maintaining composure and to help them analyze their coping skills concerning their vaccine confidence.